INTEGRASI PENDIDIKAN KARAKTER : (Studi Melalui Pembelajaran Pendidikan Agama Islam) - Murtadha Murtadha (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Integration in learning through Islamic Religious Education and character building are closely related, and must be managed properly so that educational goals can be achieved. Islamic education is the main way of forming quality human resources, having faith and piety and skilled skills. Education aims to shape the character of students as the next generation of the State. Character will shape human destiny and the welfare of a country, therefore character is very important and valuable for humans and the civilization of the people of a country. This will affect the rise of a country and affect the social changes of a country. Education is one of the pillars that support the establishment of a civilization. The existence of a citizen is largely determined by the character it has. A person who has a strong character can be dignified and respected by other countries. Becoming a country with character has become the goal of the State of Indonesia.